2020
DOI: 10.3390/nu12030600
|View full text |Cite
|
Sign up to set email alerts
|

A 12-Week-Long Intake of Bilberry Extract (Vaccinium myrtillus L.) Improved Objective Findings of Ciliary Muscle Contraction of the Eye: A Randomized, Double-Blind, Placebo-Controlled, Parallel-Group Comparison Trial

Abstract: A 12-week-long randomized, double-blind, placebo-controlled, parallel-group comparison trial was conducted to determine the effects of long-term standardized bilberry extract (SBE) intake on tonic accommodation of ciliary muscle caused by visual display terminal (VDT) tasks. This study was compliant with the accordance with CONSORT 2010 statement. A total of 109 healthy adult men and women aged 20–60 years were recruited and randomized into SBE and placebo groups. The subjects in the SBE and placebo groups wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 8 publications
0
16
0
1
Order By: Relevance
“…Individual differences in AA are large [ 10 , 11 , 12 ], but the reason remains unknown. Furthermore, it has been reported that the use of digital devices decreases AA even in young individuals [ 5 , 35 , 36 ]. The differences in DPD might be a reasonable explanation of those cases, and this should be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual differences in AA are large [ 10 , 11 , 12 ], but the reason remains unknown. Furthermore, it has been reported that the use of digital devices decreases AA even in young individuals [ 5 , 35 , 36 ]. The differences in DPD might be a reasonable explanation of those cases, and this should be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The aging of society has increased the number of people with presbyopia to 1.37 billion in 2020, which is predicted to reach 1.8 billion by 2050 [ 1 ]. The number of patients with asthenopia, neck stiffness, and headache due to the non-correction or under-correction of presbyopia has also been increasing [ 2 , 3 , 4 , 5 , 6 ], likely in part because of the widespread use of visual display terminals (VDTs) [ 7 ]. Furthermore, the worldwide loss in gross domestic product (GDP) due to the non-correction or under-correction of presbyopia in individuals younger than 65 years old was reported to be $25 billion in 2011, which is equivalent to 0.037% of the GDP [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of antioxidative supplements in preventing the progression of AMD [ 2 , 3 ], a blinding disease, have been previously reported; however, these effects were assessed and observed only in patients who already had signs of AMD, and were thus defined as high-risk patients. In contrast, the effects in the eyes of general participants with no serious diseases were reported regarding fatigue or accommodation disorders such as visual display terminal syndrome [ 6 , 32 , 33 ], dry eye disorders [ 34 ], and asthenopia [ 35 ]. Therefore, the effects were generally thought to be on mitigating the uncomfortableness rather than affecting visual acuity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the accommodative function is reported to be determined from the near-point percentage of pupillary response[24,36], and an improvement in the percentage of pupillary response can be interpreted as an improvement in the accommodative function. Clinical trials studying the consumption of anthocyanincontaining foods and eye function found that anthocyanin levels between 43.2 and 240.0 mg improved the percentage of pupillary response and the high-frequency component; both being indices of accommodative function[9,10,27,[37][38][39]. In this study, the active capsule contained 43.2 mg/day of anthocyanin.…”
mentioning
confidence: 88%
“…Bilberry (Vaccinium myrtillus) is a perennial plant of the family Ericaceae, and is found throughout the northern and eastern parts of Europe [8]. Clinical studies have shown that bilberry-derived anthocyanins aids in relieving eye fatigue [9,10] and in improving object focus, contrast sensitivity [11], and tear fluid quality [12]. Bilberry contains a higher level of anthocyanins than other berries [8].…”
Section: Introductionmentioning
confidence: 99%